2005
DOI: 10.3171/ped.2005.103.2.0137
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial volume in patients with nonsyndromal craniosynostosis

Abstract: No evidence was found that the ICVs of patients with nonsyndromal craniosynostosis are smaller than those of normal children, except for boys older than 7 months of age with metopic synostosis. This finding may have implications for the timing of surgical intervention for these patients. The indications are that interventions should be focused less on ICV and more on normalizing craniofacial shape and promoting normal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 6 publications
(6 reference statements)
5
28
0
Order By: Relevance
“…The children in the present study included only seven females, reflecting the greater incidence of sagittal craniosynostoses in boys [14]. Our current finding thus confirms the results of Netherway et al [17], who provided little evidence that the intracranial volumes of patients with non-syndromic sagittal synostosis are smaller than normal. The mean preoperative intracranial volumes in this study were similar to those obtained from agematched healthy children [12,24], although the mean postoperative intracranial volumes in this study were larger [12,24].…”
Section: Discussionsupporting
confidence: 94%
“…The children in the present study included only seven females, reflecting the greater incidence of sagittal craniosynostoses in boys [14]. Our current finding thus confirms the results of Netherway et al [17], who provided little evidence that the intracranial volumes of patients with non-syndromic sagittal synostosis are smaller than normal. The mean preoperative intracranial volumes in this study were similar to those obtained from agematched healthy children [12,24], although the mean postoperative intracranial volumes in this study were larger [12,24].…”
Section: Discussionsupporting
confidence: 94%
“…After fronto-orbital advancement, the frontal and total volumes increased, so that no statistical difference to the control group was present. Netherway et al (2005) have shown, that boys with metopic synostosis had a tendency toward smaller intracranial volumes than did healthy patients, more precisely patients younger than 7 months of age (17 boys) had normal intracranial volumes whereas patients older than 7 months (8 boys) had smaller volumes. Most recently, Maltese et al (2014) have demonstrated, that children with metopic synostosis, at least up to the ninth months, show normal intracranial volumes as a consequence of the bi-parietal widening.…”
Section: Discussionmentioning
confidence: 95%
“…The traditionally used norms of Lichtenberg (1960) are based on CT-determined data sets which were pooled for boys and girls younger than 12 months of age and several authors have already questioned their validity as a reference group (Gault et al, 1990;Netherway et al, 2005;Posnick et al, 1995). Other reference data sets for volume measurement in the first years of life are limited by small sample sizes (Abbott et al, 2000;Kamdar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Intercoronal distance can be used as a way of monitoring surgical outcome, 7 the ratio of intercoronal to interparietal distance has been used to assess the severity of frontal stenosis, 3 and intracranial volume measurement has also been suggested as an assessment tool. 8,9 In the study of Bottero et al, using the intercoronal-to-interparietal ratio, they found that cognitive delay was worse in those with severe frontal stenosis; however, the 3 grades of severity used grouped together behavioral disturbances, IQ, and speech and language assessments, and no formal speech and language assessments were independently compared with the degree of stenosis in their study. The ratio of intercoronal to interparietal distances might reflect the overall volume of the cranium rather than a localized constriction.…”
Section: Discussionmentioning
confidence: 96%